Eavesdropping on Missing Data: What Are University Students Doing When They Miss Experience Sampling Reports?. (November 2021) - Sun, Jessie; Rhemtulla, Mijke; Vazire, Simine
Participants in experience sampling method (ESM) studies are "beeped" several times per day to report on their momentary experiences—but participants do not always answer the beep. Knowing whether there are systematic predictors of missing a report is critical for understanding the extent to which missing data threatens the validity of inferences from ESM studies. Here, 228 university students completed up to four ESM reports per day while wearing the Electronically Activated Recorder (EAR)—an unobtrusive audio recording device—for a week. These audio recordings provided an alternative source of information about what participants were doing when they missed or completed reports (3, 678 observations). We predicted missing ESM reports from 46 variables coded from the EAR recordings, and found very little evidence that missing an ESM report was correlated with constructs typically of interest to ESM researchers. These findings provide reassuring evidence for the validity of ESM research among relatively healthy university student samples.